Bio-based packaging material and preparation method thereof
Patent Information
- Application Number
- CN202411835422.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-13
Smart Images

Figure BDA0005186570280000031 
Figure FDA0005186570270000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, in particular to a bio-based packaging material and a preparation method thereof. Background Art
[0002] Since the new century, the global economy and technology have developed rapidly, people's demand for a better life has increased successively, and the application of petroleum products has become more and more extensive. The polyester industry, which is mainly based on petrochemical resources, has continued to develop, making polymer materials, as extremely versatile and diverse structures, play a prominent role in multifunctional polyester materials, which are not only available on a practical industrial scale, but also meet the needs of daily life.
[0003] In the context of serious white pollution caused by petroleum-based plastics, bio-based packaging plastics in the packaging industry have received extensive attention from scholars. The raw materials of bio-based packaging materials are partially or completely processed and polymerized by biochemical or physical means from crops or trees in nature. Bacteria convert these raw materials into various monomers required for polymer production through biological action. Compared with petroleum-based packaging materials made from oil and natural gas, bio-based packaging materials are more environmentally friendly, such as polylactic acid, chitosan and starch. 2,5-Furandicarboxylic acid is obtained from biomass resources such as cellulose or sugars. The bio-based polyester materials synthesized from 2,5-Furandicarboxylic acid have excellent properties and broad development prospects. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a bio-based packaging material to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A bio-based packaging material, wherein the bio-based packaging material is prepared by reacting 6-maleimido-1-hexanal and bis(3-aminopropyl)phenylphosphine to obtain a flame retardant crosslinking agent; reacting N-(2-bromoethyl)maleimide and chitosan to obtain modified chitosan; reacting zinc oxide with [3-(trimethoxysilyl)propyl]succinic anhydride and then with modified chitosan, and finally quaternizing with iodomethane to obtain modified zinc oxide; reacting 2,5-furandicarboxylic acid and propylene glycol to obtain furan copolyester; and mixing, molding and heat-insulating the flame retardant crosslinking agent, modified zinc oxide and furan copolyester to obtain the material.
[0007] A method for preparing a bio-based packaging material comprises the following steps:
[0008] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol are mixed in a mass ratio of 1:(0.5-0.7):(4-8), stirred at 75-85°C and 200-300 r / min for 1.5-2.5 hours, filtered, washed the residue with anhydrous ethanol for 3-5 times, and vacuum dried at 55-65°C for 4-6 hours to obtain a flame retardant crosslinking agent;
[0009] (2) [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol are mixed in a mass ratio of 1:(2-4):(15-25), stirred at 200-300 r / min at 60-70° C. and heated in a water bath for 0.5-1.5 h, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 3-5 times, and vacuum dried at 55-65° C. for 4-6 h to obtain primary modified zinc oxide;
[0010] (3) Pre-modified zinc oxide, modified chitosan and N,N-dimethylformamide are mixed in a mass ratio of 1:
[0011] (1.2-1.4): (10-20) mix well, stir at 75-85°C and 500-700r / min for 8-10h under nitrogen atmosphere, cool to room temperature, add chloroform with 2-3 times the mass of anhydrous ethanol, continue stirring for 25-35min, filter, wash the filter residue with anhydrous ethanol for 3-5 times, and vacuum dry at 55-65°C for 4-6h to obtain chitosan-modified zinc oxide; Zinc oxide, methyl iodide, sodium hydroxide, sodium iodide and N-methyl-pyrrolidone are mixed in a mass ratio of 1: (0.4-0.6): (0.1-0.2): (0.04-0.06): (5-7), stirred at room temperature at 500-700 r / min for 4-6 hours, filtered, and the filter residue is washed with deionized water and anhydrous ethanol for 3-5 times respectively, and vacuum dried at 55-65°C for 4-6 hours to obtain modified zinc oxide;
[0012] (4) 2,5-furandicarboxylic acid and propylene glycol are mixed in a molar ratio of 1:(1.5-1.7) and added to a reaction kettle at a temperature of 205-215° C., tetrabutyl titanate in an amount of 0.002-0.004 times the mass of 2,5-furandicarboxylic acid is added, nitrogen is introduced, stirring at 500-700 r / min for 3-4 hours, the temperature is raised to 225-235° C., vacuum is slowly drawn to 60-200 Pa, stirring is continued, and the material is discharged when a climbing pole effect occurs to obtain a furan copolyester;
[0013] (5) Add furan copolyester, modified zinc oxide, and flame retardant crosslinking agent in a mass ratio of 1:(0.1-0.3):(0.1-0.3) into a torque rheometer for internal kneading, and then use a mold for compression molding, and keep the temperature at 50°C for 48 hours to obtain a bio-based packaging material.
[0014] The method for preparing a bio-based packaging material according to claim 2 is characterized in that the reaction process of the flame retardant cross-linking agent in step (1) is as follows:
[0015]
[0016] As an optimization, the preparation method of the modified chitosan described in step (2) is: N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol are mixed in a mass ratio of 1: (1-1.2): (0.2-0.4): (10-20), stirred at 55-65°C at 300-500 r / min for 3-5 hours, cooled to room temperature, filtered, washed the residue with anhydrous ethanol for 3-5 times, and vacuum dried at 55-65°C for 4-6 hours.
[0017] As an optimization, the chitosan in step (2) is chitosan with a deacetylation degree of 85%.
[0018] As an optimization, the zinc oxide described in step (2) is industrial grade zinc oxide.
[0019] As an optimization, the process parameters of the internal mixing in step (5) are: temperature 65-75°C, time 10-20 min, and screw speed 100 r / min.
[0020] As an optimization, the molding process parameters of step (5) are: hot pressing temperature 125-135°C, hot pressing time 30-40 min, pressure 7-10 MPa, and cold pressing time 10 min.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] When preparing the bio-based packaging material, the present invention comprises the following steps: 6-maleimido-1-hexanal and bis(3-aminopropyl)phenylphosphine are reacted to obtain a flame retardant crosslinking agent; N-(2-bromoethyl)maleimide and chitosan are reacted to obtain modified chitosan; zinc oxide is first reacted with [3-(trimethoxysilyl)propyl]succinic anhydride and then with modified chitosan, and finally quaternized with iodomethane to obtain modified zinc oxide; 2,5-furandicarboxylic acid and propylene glycol are reacted to obtain furan copolyester; and the flame retardant crosslinking agent, modified zinc oxide and furan copolyester are mixed, molded and heat-insulated to obtain the bio-based packaging material.
[0023] Firstly, 6-maleimido-1-hexanal and bis(3-aminopropyl)phenylphosphine are used to prepare a flame retardant crosslinking agent, wherein bis(3-aminopropyl)phenylphosphine introduces phosphorus into the bio-based packaging material, which can promote the formation of a dense carbon layer on the surface of the material during the combustion process. The dense carbon layer can block the transfer of heat and oxygen, reduce the combustion inside the material, and thus improve the flame retardant properties of the bio-based packaging material; 6-maleimido-1-hexanal introduces a bismaleimide structure, which can undergo a thermally reversible Diels-Alder reaction with furan on the furan copolyester, produce chemical crosslinking with the furan copolyester, effectively increase the crosslinking density, and thus improve the tensile properties of the bio-based packaging material; and the thermally reversible Diels-Alder reaction enables the bio-based packaging material to be re-prepared into a material with no significant decrease in mechanical properties after being recycled through melt molding, thereby having recyclability.
[0024] Secondly, N-(2-bromoethyl)maleimide reacts with chitosan to obtain modified chitosan, zinc oxide first reacts with [3-(trimethoxysilyl)propyl]succinic anhydride and then reacts with modified chitosan, and finally is quaternized with iodomethane to obtain modified zinc oxide. The maleimide structure introduced on the modified chitosan can undergo a thermally reversible Diels-Alder reaction with furan on the furan copolyester, further improving the tensile properties and recyclability; iodomethane reacts with amino groups to produce quaternary ammonium salts. Quaternary ammonium salts have good contact antibacterial effects as cationic antibacterial agents, thereby improving the antibacterial properties of bio-based packaging materials. Zinc oxide can produce free radicals to destroy bacterial cell walls and cell membranes, inhibit bacterial growth and reproduction, and further improve the antibacterial properties of bio-based packaging materials. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] A method for preparing a bio-based packaging material comprises the following steps:
[0028] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol were mixed in a mass ratio of 1:0.5:4, stirred at 75°C and 200 r / min for 1.5 h, filtered, and the residue was washed with anhydrous ethanol for 3 times, and vacuum dried at 55°C for 4 h to prepare a flame retardant crosslinking agent;
[0029] (2) N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol were mixed in a mass ratio of 1:1:0.2:10, stirred at 300 r / min for 3 h at 55°C, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 3 times, and vacuum dried at 55°C for 4 h to obtain modified chitosan; [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:2:15, stirred at 200 r / min at 60°C and heated in a water bath for 0.5 h, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 3 times, and vacuum dried at 55°C for 4 h to obtain primary modified zinc oxide;
[0030] (3) The primary modified zinc oxide, modified chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.2:10, stirred at 75°C and 500 r / min for 8 h under a nitrogen atmosphere, cooled to room temperature, and chloroform twice the mass of anhydrous ethanol was added, and stirring was continued for 25 min. The mixture was filtered, and the residue was washed with anhydrous ethanol for 3 times, and vacuum dried at 55°C for 4 h to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.4:0.1:0.04:5, stirred at room temperature for 4 h at 500 r / min, filtered, and the residue was washed with deionized water and anhydrous ethanol for 3 times, and vacuum dried at 55°C for 4 h to obtain modified zinc oxide;
[0031] (4) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.5 and added to a reactor at a temperature of 205° C., tetrabutyl titanate (0.002 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, stirred at 500 r / min for 3 h, the temperature was raised to 225° C., vacuumed slowly to 60 Pa, and stirring was continued. When the climbing pole effect occurred, the material was discharged to obtain furan copolyester;
[0032] (5) Furan copolyester, modified zinc oxide, and flame retardant crosslinking agent were added to the torque rheometer at a mass ratio of 1:0.1:0.1 for internal kneading. The internal kneading process parameters were set as follows: temperature 65°C, time 10 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 125°C, hot pressing time 30 min, pressure 7 MPa, cold pressing time 10 min, and heat preservation at 50°C for 48 h to obtain a bio-based packaging material.
[0033] Embodiment 2:
[0034] A method for preparing a bio-based packaging material comprises the following steps:
[0035] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol were mixed in a mass ratio of 1:0.6:6, stirred at 80°C and 250 r / min for 2 h, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to prepare a flame retardant crosslinking agent;
[0036] (2) N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol were mixed in a mass ratio of 1:1.1:0.3:15, stirred at 400 r / min at 60°C for 4 h, cooled to room temperature, filtered, washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified chitosan; [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:3:20, stirred at 250 r / min at 65°C and heated in a water bath for 1 h, cooled to room temperature, filtered, washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain primary modified zinc oxide;
[0037] (3) The primary modified zinc oxide, modified chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:15, stirred at 80°C and 600 r / min for 9 hours under a nitrogen atmosphere, cooled to room temperature, and chloroform (2.5 times the mass of anhydrous ethanol) was added, and stirring was continued for 30 minutes. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 hours to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.5:0.15:0.05:6, stirred at room temperature for 5 hours at 600 r / min, filtered, and the residue was washed with deionized water and anhydrous ethanol for 4 times, respectively, and vacuum dried at 60°C for 5 hours to obtain modified zinc oxide;
[0038] (4) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.6 and added to a reactor at a temperature of 210° C., tetrabutyl titanate (0.003 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, and the mixture was stirred at 600 r / min for 3.5 h. The mixture was heated to 230° C. and slowly evacuated to 130 Pa. The mixture was stirred continuously. When the climbing pole effect occurred, the mixture was discharged to obtain furan copolyester.
[0039] (5) Furan copolyester, modified zinc oxide, and flame retardant crosslinking agent were added to the torque rheometer at a mass ratio of 1:0.2:0.2 for internal kneading. The internal kneading process parameters were set as follows: temperature 70°C, time 15 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 130°C, hot pressing time 35 min, pressure 8.5 MPa, cold pressing time 10 min, and kept warm at 50°C for 48 h to obtain a bio-based packaging material.
[0040] Embodiment 3:
[0041] A method for preparing a bio-based packaging material comprises the following steps:
[0042] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol were mixed in a mass ratio of 1:0.7:8, stirred at 85°C and 300 r / min for 2.5 hours, filtered, and the residue was washed with anhydrous ethanol for 5 times, and vacuum dried at 65°C for 6 hours to prepare a flame retardant crosslinking agent;
[0043] (2) N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol were mixed in a mass ratio of 1:1.2:0.4:20, stirred at 65°C and 500 r / min for 5 h, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 5 times, and vacuum dried at 65°C for 6 h to obtain modified chitosan; [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:4:25, stirred at 70°C at a rate of 300 r / min and heated in a water bath for 1.5 h, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 5 times, and vacuum dried at 65°C for 6 h to obtain primary modified zinc oxide;
[0044] (3) The primary modified zinc oxide, modified chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.4:20, stirred at 85°C and 700 r / min for 10 h under a nitrogen atmosphere, cooled to room temperature, and chloroform was added in an amount 3 times the mass of anhydrous ethanol, and the stirring was continued for 35 min. The mixture was filtered, and the residue was washed with anhydrous ethanol for 5 times, and vacuum dried at 65°C for 6 h to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.6:0.2:0.06:7, stirred at room temperature at 700 r / min for 6 h, filtered, and the residue was washed with deionized water and anhydrous ethanol for 5 times, respectively, and vacuum dried at 65°C for 6 h to obtain modified zinc oxide;
[0045] (4) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.7 and added into a reactor at a temperature of 215° C., tetrabutyl titanate (0.004 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, stirred at 700 r / min for 4 h, the temperature was raised to 235° C., vacuumed slowly to 200 Pa, and stirring was continued. When the climbing pole effect occurred, the material was discharged to obtain furan copolyester;
[0046] (5) Furan copolyester, modified zinc oxide, and flame retardant crosslinking agent were added to the torque rheometer at a mass ratio of 1:0.3:0.3 for internal kneading, and the internal kneading process parameters were set as follows: temperature 75°C, time 20 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 135°C, hot pressing time 40 min, pressure 10 MPa, cold pressing time 10 min, and heat preservation at 50°C for 48 h to obtain a bio-based packaging material.
[0047] Comparative Example 1:
[0048] A method for preparing a bio-based packaging material comprises the following steps:
[0049] (1) N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol were mixed in a mass ratio of 1:1.1:0.3:15, stirred at 400 r / min for 4 h at 60°C, cooled to room temperature, filtered, washed the residue with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified chitosan; [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:3:20, stirred at 250 r / min at 65°C and heated in a water bath for 1 h, cooled to room temperature, filtered, washed the residue with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain primary modified zinc oxide;
[0050] (2) The primary modified zinc oxide, modified chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:15, stirred at 80°C and 600 r / min for 9 h under a nitrogen atmosphere, cooled to room temperature, and chloroform (2.5 times the mass of anhydrous ethanol) was added, and stirring was continued for 30 min. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.5:0.15:0.05:6, stirred at room temperature for 5 h at 600 r / min, filtered, and the residue was washed with deionized water and anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified zinc oxide;
[0051] (3) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.6 and added to a reactor at a temperature of 210° C., tetrabutyl titanate (0.003 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, and the mixture was stirred at 600 r / min for 3.5 h. The mixture was heated to 230° C. and slowly evacuated to 130 Pa. The mixture was stirred continuously. When the climbing pole effect occurred, the mixture was discharged to obtain furan copolyester.
[0052] (4) Furan copolyester, modified zinc oxide, and bis(3-aminopropyl)phenylphosphine were added to the torque rheometer at a mass ratio of 1:0.2:0.1 for internal kneading. The internal kneading process parameters were set as follows: temperature 70°C, time 15 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 130°C, hot pressing time 35 min, pressure 8.5 MPa, cold pressing time 10 min, and kept warm at 50°C for 48 h to obtain a bio-based packaging material.
[0053] Comparative Example 2:
[0054] A method for preparing a bio-based packaging material comprises the following steps:
[0055] (1) N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol were mixed in a mass ratio of 1:1.1:0.3:15, stirred at 400 r / min for 4 h at 60°C, cooled to room temperature, filtered, washed the residue with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified chitosan; [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:3:20, stirred at 250 r / min at 65°C and heated in a water bath for 1 h, cooled to room temperature, filtered, washed the residue with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain primary modified zinc oxide;
[0056] (2) The primary modified zinc oxide, modified chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:15, stirred at 80°C and 600 r / min for 9 h under a nitrogen atmosphere, cooled to room temperature, and chloroform (2.5 times the mass of anhydrous ethanol) was added, and stirring was continued for 30 min. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.5:0.15:0.05:6, stirred at room temperature for 5 h at 600 r / min, filtered, and the residue was washed with deionized water and anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified zinc oxide;
[0057] (3) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.6 and added to a reactor at a temperature of 210° C., tetrabutyl titanate (0.003 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, and the mixture was stirred at 600 r / min for 3.5 h. The mixture was heated to 230° C. and slowly evacuated to 130 Pa. The mixture was stirred continuously. When the climbing pole effect occurred, the mixture was discharged to obtain furan copolyester.
[0058] (4) Furan copolyester and modified zinc oxide were added to the torque rheometer at a mass ratio of 1:0.2 for internal kneading, and the internal kneading process parameters were set as follows: temperature 70°C, time 15 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 130°C, hot pressing time 35 min, pressure 8.5 MPa, cold pressing time 10 min, and kept warm at 50°C for 48 h to obtain a bio-based packaging material.
[0059] Comparative Example 3:
[0060] A method for preparing a bio-based packaging material comprises the following steps:
[0061] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol were mixed in a mass ratio of 1:0.6:6, stirred at 80°C and 250 r / min for 2 h, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to prepare a flame retardant crosslinking agent;
[0062] (2) [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:3:20, stirred at 65°C at a rate of 250 r / min and heated in a water bath for 1 h, cooled to room temperature, filtered, and the filter residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain primary modified zinc oxide;
[0063] (3) The primary modified zinc oxide, chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:15, stirred at 80°C and 600 r / min for 9 hours under a nitrogen atmosphere, cooled to room temperature, and chloroform was added in an amount 2.5 times the mass of anhydrous ethanol, and the stirring was continued for 30 minutes. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 hours to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.5:0.15:0.05:6, stirred at room temperature for 5 hours at 600 r / min, filtered, and the residue was washed with deionized water and anhydrous ethanol for 4 times, respectively, and vacuum dried at 60°C for 5 hours to obtain modified zinc oxide;
[0064] (4) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.6 and added to a reactor at a temperature of 210° C., tetrabutyl titanate (0.003 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, and the mixture was stirred at 600 r / min for 3.5 h. The mixture was heated to 230° C. and slowly evacuated to 130 Pa. The mixture was stirred continuously. When the climbing pole effect occurred, the mixture was discharged to obtain furan copolyester.
[0065] (5) Furan copolyester, modified zinc oxide, and flame retardant crosslinking agent were added to the torque rheometer at a mass ratio of 1:0.2:0.2 for internal kneading. The internal kneading process parameters were set as follows: temperature 70°C, time 15 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 130°C, hot pressing time 35 min, pressure 8.5 MPa, cold pressing time 10 min, and kept warm at 50°C for 48 h to obtain a bio-based packaging material.
[0066] Comparative Example 4:
[0067] A method for preparing a bio-based packaging material comprises the following steps:
[0068] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol were mixed in a mass ratio of 1:0.6:6, stirred at 80°C and 250 r / min for 2 h, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to prepare a flame retardant crosslinking agent;
[0069] (2) N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol were mixed in a mass ratio of 1:1.1:0.3:15, stirred at 400 r / min at 60°C for 4 h, cooled to room temperature, filtered, washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified chitosan; [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol were mixed in a mass ratio of 1:3:20, stirred at 250 r / min at 65°C and heated in a water bath for 1 h, cooled to room temperature, filtered, washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain primary modified zinc oxide;
[0070] (3) The primary modified zinc oxide, modified chitosan and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:15, stirred at 80°C and 600 r / min for 9 h under a nitrogen atmosphere, cooled to room temperature, added chloroform with a mass of 2.5 times that of anhydrous ethanol, continued to stir for 30 min, filtered, washed the filter residue with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain chitosan modified zinc oxide;
[0071] (4) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.6 and added to a reactor at a temperature of 210° C., tetrabutyl titanate (0.003 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, and the mixture was stirred at 600 r / min for 3.5 h. The mixture was heated to 230° C. and slowly evacuated to 130 Pa. The mixture was stirred continuously. When the climbing pole effect occurred, the mixture was discharged to obtain furan copolyester.
[0072] (5) Furan copolyester, chitosan modified zinc oxide, and flame retardant crosslinking agent were added into the torque rheometer at a mass ratio of 1:0.2:0.2 for internal kneading. The internal kneading process parameters were set as follows: temperature 70°C, time 15 min, screw speed 100 r / min, and then molded with a mold. The molding parameters were set as follows: hot pressing temperature 130°C, hot pressing time 35 min, pressure 8.5 MPa, cold pressing time 10 min, and kept warm at 50°C for 48 h to obtain a bio-based packaging material.
[0073] Comparative Example 5:
[0074] A method for preparing a bio-based packaging material comprises the following steps:
[0075] (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol were mixed in a mass ratio of 1:0.6:6, stirred at 80°C and 250 r / min for 2 h, filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to prepare a flame retardant crosslinking agent;
[0076] (2) The primary modified zinc oxide, modified chitosan, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:15, stirred at 80°C and 600 r / min for 9 h under a nitrogen atmosphere, cooled to room temperature, and chloroform (2.5 times the mass of anhydrous ethanol) was added, and stirring was continued for 30 min. The mixture was filtered, and the residue was washed with anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain chitosan-modified zinc oxide; chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone were mixed in a mass ratio of 1:0.5:0.15:0.05:6, stirred at room temperature for 5 h at 600 r / min, filtered, and the residue was washed with deionized water and anhydrous ethanol for 4 times, and vacuum dried at 60°C for 5 h to obtain modified zinc oxide;
[0077] (3) 2,5-furandicarboxylic acid and propylene glycol were mixed in a molar ratio of 1:1.6 and added to a reactor at a temperature of 210° C., tetrabutyl titanate (0.003 times the mass of 2,5-furandicarboxylic acid) was added, nitrogen was introduced, and the mixture was stirred at 600 r / min for 3.5 h. The mixture was heated to 230° C. and slowly evacuated to 130 Pa. The mixture was stirred continuously. When the climbing pole effect occurred, the mixture was discharged to obtain furan copolyester.
[0078] (4) Furan copolyester and flame retardant crosslinking agent were added into the torque rheometer at a mass ratio of 1:0.2 for internal kneading. The internal kneading process parameters were set as follows: temperature 70°C, time 15 min, screw speed 100 r / min. The mixture was then molded using a mold. The molding parameters were set as follows: hot pressing temperature 130°C, hot pressing time 35 min, pressure 8.5 MPa, cold pressing time 10 min, and heat preservation at 50°C for 48 h to obtain a bio-based packaging material.
[0079] Test Example 1:
[0080] Tensile property test: Each embodiment and comparative example was prepared into a standard specimen with a specification of 75×4.3×1 mm. The specimen was placed in a drying dish for 48 hours before testing to eliminate internal stress. The tensile test was performed using a ZwickRoell Z020 universal material testing machine, with the test speed set to 20 mm / min and the force sensor set to 500 N. The breaking strength was recorded as 1. The results are shown in Table 1.
[0081] Recyclability test: The bio-based packaging materials of each embodiment and comparative example were cut into small particles, and repeatedly hot-pressed into a square thin plate of about 1 mm thick using a 100×120×1mm mold on a water-cooled electric vulcanizing molding machine (High-speed Railway Detection Instrument Co., Ltd.), the hot pressing temperature was 130°C, the hot pressing time was 30min, and then cold pressed for 10min to obtain a square thin plate; the square thin plate was kept at a constant temperature of 50°C at normal pressure in a vacuum oven for 48h, and cut according to the specifications of 75×4.3×1mm to obtain a recycling test specimen. The recycled test specimen was placed in a drying dish for 48h before the test to eliminate internal stress. The tensile test was performed using a ZwickRoell Z020 universal material testing machine, with the test speed set to 20mm / min and the force sensor set to 500N. The breaking strength was recorded as 2. The results are shown in Table 1.
[0082] Table 1
[0083] Breaking strength 1 Breaking strength 2 Breaking strength 1 Breaking strength 2 Example 1 28.6MPa 28.5MPa Comparative Example 1 22.7MPa 18.7MPa Example 2 28.9MPa 29.0MPa Comparative Example 2 22.5MPa 18.5MPa Example 3 29.0MPa 28.8MPa Comparative Example 3 25.1MPa 22.3MPa Comparative Example 4 28.7MPa 28.5MPa Comparative Example 5 25.5MPa 22.5MPa
[0084] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the bio-based packaging material prepared by the present invention has good tensile properties and recyclability.
[0085] By comparison, the breaking strength 1 of Examples 1 to 3 is greater than the breaking strength 1 of Comparative Examples 1 and 2, indicating that the bismaleimide on the flame retardant crosslinker can undergo a Diels-Alder reaction with the furan on the furan copolyester, produce chemical crosslinks with the furan copolyester, and effectively increase the crosslinking density, thereby improving the tensile properties of the bio-based packaging material.
[0086] By comparison, the difference between the breaking strength 2 and the breaking strength 1 of Examples 1 to 3 is smaller than the difference between the breaking strength 2 and the breaking strength 1 of Comparative Examples 1, 2, 5, and 5, indicating that the thermally reversible Diels-Alder reaction between furan and maleimide enables the bio-based packaging material to be re-melted and molded after recycling, and a material with no significant decrease in mechanical properties can be obtained, thereby having recyclability.
[0087] Test Example 2:
[0088] Antibacterial performance test: The materials of each embodiment and comparative example were crushed into powders of less than 150 microns, and the same mass was taken to test the antibacterial rate of the materials against Staphylococcus aureus according to the Quine test method. The results are shown in Table 2.
[0089] Table 2
[0090] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.1 Comparative Example 1 99.2 Example 2 98.9 Comparative Example 2 99.1 Example 3 99.4 Comparative Example 3 98.9 Comparative Example 4 43.5 Comparative Example 5 11.7
[0091] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the bio-based packaging material prepared by the present invention has good antibacterial properties.
[0092] By comparison, the antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 4, indicating that the amino groups on the modified chitosan react with N-(2-bromoethyl)maleimide and are then quaternized with iodomethane to generate quaternary ammonium salts. Quaternary ammonium salts, as cationic antibacterial agents, have good contact antibacterial effects, thereby improving the antibacterial properties of bio-based packaging materials. The antibacterial rates of Examples 1 to 3 are significantly greater than that of Comparative Example 5, indicating that the free radicals generated by zinc oxide can effectively destroy the cell walls and cell membranes of bacteria, inhibit the growth and reproduction of bacteria, and thus improve the antibacterial properties of the material.
[0093] Test Example 3:
[0094] Flame retardant performance test: The bio-based packaging materials obtained in each embodiment and test example were prepared into samples according to GB / T2406 and tested for limiting oxygen index. The results are shown in Table 3.
[0095] Table 3
[0096] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 33.8 Comparative Example 1 33.7 Example 2 34.1 Comparative Example 2 21.6 Example 3 33.9 Comparative Example 3 33.8 Comparative Example 4 33.9 Comparative Example 5 33.4
[0097] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the bio-based packaging material prepared by the present invention has good flame retardant properties.
[0098] By comparison, the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 2, indicating that the introduction of phosphorus element by bis(3-aminopropyl)phenylphosphine into the bio-based packaging material can promote the formation of a dense carbon layer on the surface of the material during the combustion process. The dense carbon layer can block the transfer of heat and oxygen, reduce combustion inside the material, and thus improve the flame retardant properties of the bio-based packaging material.
[0099] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A bio-based packaging material, characterized in that: The bio-based packaging material is prepared by mixing, molding and heat-insulating a flame retardant cross-linking agent, modified zinc oxide and furan copolyester; The flame retardant crosslinking agent is prepared by reacting 6-maleimido-1-hexanal and bis(3-aminopropyl)phenylphosphine; The modified zinc oxide is firstly prepared by reacting N-(2-bromoethyl)maleimide with chitosan to obtain modified chitosan, then reacting zinc oxide with [3-(trimethoxysilyl)propyl]succinic anhydride and modified chitosan, and finally quaternizing with iodomethane to obtain the modified zinc oxide. The furan copolyester is prepared by reacting 2,5-furandicarboxylic acid and propylene glycol.
2. A method for preparing a bio-based packaging material, characterized in that: The method comprises the following preparation steps: (1) 6-maleimido-1-hexanal, bis(3-aminopropyl)phenylphosphine and anhydrous ethanol are mixed in a mass ratio of 1:(0.5-0.7):(4-8), stirred at 75-85°C and 200-300 r / min for 1.5-2.5 hours, filtered, washed the residue with anhydrous ethanol for 3-5 times, and vacuum dried at 55-65°C for 4-6 hours to obtain a flame retardant crosslinking agent; (2) [3-(trimethoxysilyl)propyl]succinic anhydride, nano zinc oxide, and anhydrous ethanol are mixed in a mass ratio of 1:(2-4):(15-25), stirred at 200-300 r / min at 60-70° C. and heated in a water bath for 0.5-1.5 h, cooled to room temperature, filtered, and the residue was washed with anhydrous ethanol for 3-5 times, and vacuum dried at 55-65° C. for 4-6 h to obtain primary modified zinc oxide; (3) Pre-modified zinc oxide, modified chitosan and N,N-dimethylformamide are mixed in a mass ratio of 1: (1.2-1.4): (10-20) mix well, stir at 75-85°C and 500-700 r / min for 8-10 h under nitrogen atmosphere, cool to room temperature, add chloroform 2-3 times the mass of anhydrous ethanol, continue stirring for 25-35 min, filter, wash the filter residue with anhydrous ethanol for 3-5 times, and vacuum dry at 55-65°C for 4-6 h to obtain chitosan modified zinc oxide; Chitosan-modified zinc oxide, methyl iodide, sodium hydroxide, sodium iodide, and N-methyl-pyrrolidone are mixed in a mass ratio of 1: (0.4-0.6): (0.1-0.2): (0.04-0.06): (5-7), stirred at room temperature at 500-700 r / min for 4-6 hours, filtered, and the residue is washed with deionized water and anhydrous ethanol for 3-5 times, respectively, and vacuum dried at 55-65° C. for 4-6 hours to obtain modified zinc oxide; (4) 2,5-furandicarboxylic acid and propylene glycol are mixed in a molar ratio of 1:(1.5-1.7) and added to a reaction kettle at a temperature of 205-215° C., tetrabutyl titanate in an amount of 0.002-0.004 times the mass of 2,5-furandicarboxylic acid is added, nitrogen is introduced, stirring at 500-700 r / min for 3-4 hours, the temperature is raised to 225-235° C., vacuum is slowly drawn to 60-200 Pa, stirring is continued, and the material is discharged when a climbing pole effect occurs to obtain a furan copolyester; (5) Add furan copolyester, modified zinc oxide, and flame retardant crosslinking agent in a mass ratio of 1:(0.1-0.3):(0.1-0.3) into a torque rheometer for internal kneading, and then use a mold for compression molding, and keep the temperature at 50°C for 48 hours to obtain a bio-based packaging material.
3. The method for preparing a bio-based packaging material according to claim 2, characterized in that: The reaction process of the flame retardant crosslinking agent in step (1) is as follows:
4. The method for preparing a bio-based packaging material according to claim 2, characterized in that: The preparation method of the modified chitosan described in step (2) is: N-(2-bromoethyl)maleimide, chitosan, triethylamine, and anhydrous ethanol are mixed in a mass ratio of 1: (1-1.2): (0.2-0.4): (10-20), stirred at 300-500 r / min for 3-5 hours at 55-65° C., cooled to room temperature, filtered, washed the filter residue with anhydrous ethanol for 3-5 times, and vacuum dried at 55-65° C. for 4-6 hours to obtain the obtained product.
5. The method for preparing a bio-based packaging material according to claim 2, characterized in that: The chitosan described in step (2) is chitosan with a deacetylation degree of 85%.
6. The method for preparing a bio-based packaging material according to claim 2, characterized in that: The zinc oxide described in step (2) is industrial grade zinc oxide.
7. The method for preparing a bio-based packaging material according to claim 2, characterized in that: The process parameters of the banburying in step (5) are: temperature 65-75° C., time 10-20 min, and screw speed 100 r / min.
8. The method for preparing a bio-based packaging material according to claim 2, characterized in that: The molding process parameters of step (5) are: hot pressing temperature 125-135° C., hot pressing time 30-40 min, pressure 7-10 MPa, and cold pressing time 10 min.
Citation Information
Patent Citations
Preparation method of high-toughness bio-based antibacterial polyester
CN111621006A
Preparation method of bio-based polyester with antibacterial property
CN111635516A
Heat-resistant flame-retardant polyester, polyester product, and preparation method and application thereof
CN111777753A
Bio-based heat-resistant flame-retardant polyester, polyester product, preparation method and application thereof
CN111808271A
Droplet-resistant flame-retardant modified polyester and preparation method thereof
CN112239588A